Śląska ortografia ślabikŏrzowa – status, forma, funkcjonowanie - Jaroszewicz, Henryk (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*66.03px); top: calc(var(--scale-factor)*202.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03711);" role="presentation">In the contemporary Silesian-language communicative space, the dominant role is <span dir="ltr" style="left: calc(var(--scale-factor)*66.43px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.967799);" role="presentation">played by <span dir="ltr" style="left: calc(var(--scale-factor)*106.29px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03191);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*120.86px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.978226);" role="presentation">ślabikŏrzowa <span dir="ltr" style="left: calc(var(--scale-factor)*174.98px); top: calc(var(--scale-factor)*216.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.976319);" role="presentation">orthography, i.e. the way of writing developed at the end of <span dir="ltr" style="left: calc(var(--scale-factor)*66.32px); top: calc(var(--scale-factor)*230.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.98987);" role="presentation">the first decade of the twenty-first century. This spelling system is used in most recent <span dir="ltr" style="left: calc(var(--scale-factor)*66.13px); top: calc(var(--scale-factor)*244.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.993097);" role="presentation">Silesian-language publications, advertising language, electronic media, computer soft<span dir="ltr" style="left: calc(var(--scale-factor)*66.04px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.983059);" role="presentation">ware and smartphones. The <span dir="ltr" style="left: calc(var(--scale-factor)*175.92px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.963082);" role="presentation">ślabikŏrzowa <span dir="ltr" style="left: calc(var(--scale-factor)*229.05px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.970542);" role="presentation">orthography owes its privileged position <span dir="ltr" style="left: calc(var(--scale-factor)*387.73px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00601);" role="presentation">to <span dir="ltr" style="left: calc(var(--scale-factor)*397.33px); top: calc(var(--scale-factor)*258.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.968873);" role="presentation">its <span dir="ltr" style="left: calc(var(--scale-factor)*66.36px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.99804);" role="presentation">conservative form, the presence of clear and straightforward rules of usage and a <span dir="ltr" style="left: calc(var(--scale-factor)*391.09px); top: calc(var(--scale-factor)*272.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.988659);" role="presentation">rela<span dir="ltr" style="left: calc(var(--scale-factor)*66.32px); top: calc(var(--scale-factor)*286.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.971521);" role="presentation">tively strong organisational, intellectual, scientific and economic background. However, <span dir="ltr" style="left: calc(var(--scale-factor)*66.32px); top: calc(var(--scale-factor)*300.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00747);" role="presentation">the further development of <span dir="ltr" style="left: calc(var(--scale-factor)*176.15px); top: calc(var(--scale-factor)*300.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.963419);" role="presentation">ślabikŏrzowy <span dir="ltr" style="left: calc(var(--scale-factor)*230.19px); top: calc(var(--scale-factor)*300.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.996981);" role="presentation">literature is hampered by <span dir="ltr" style="left: calc(var(--scale-factor)*331.70px); top: calc(var(--scale-factor)*300.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.980228);" role="presentation">the lack of detailed <span dir="ltr" style="left: calc(var(--scale-factor)*66.30px); top: calc(var(--scale-factor)*314.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999168);" role="presentation">normative materials (i.e. spelling dictionary, grammar).